Assessment of intraretinal hyperreflective foci using multimodal imaging in eyes with age‐related macular degeneration - Oncel, Deniz; Corradetti, Giulia; He, Ye; Ashrafkhorasani, Maryam; Nittala, Muneeswar Gupta; Stambolian, Dwight; Pericak‐Vance, Margaret A.; Haines, Jonathan L.; Sadda, Srinivas R. (Acta ophthalmologica (Oxford, England), 2024)
Purpose This study aimed to investigate the correspondence between intraretinal hyperreflective foci (IHRF) identified on optical coherence tomography (OCT) B‐scans with hyperpigmentation on colour fundus photography (CFP) or hyperreflectivity on infrared reflectance (IR) images in eyes with age‐related macular degeneration (AMD). Methods Flash CFP, IR images and OCT B‐scans obtained at the same visit were evaluated. Individual IHRF identified on OCT B‐scans were assessed for the qualitative presence or absence of a hypotransmission tail into the choroid. The corresponding IR image obtained at the time of OCT acquisition was analysed for the presence or absence of hyperreflectivity in this region. The IR images were manually registered to the CFP image, and CFP images were inspected for the presence or absence of hyperpigmentation at the location of IHRF. Results From 122 eyes, a total of 494 IHRF were evaluated. For the primary analysis of qualitative presence or absence of hyperpigmentation on CFP and hyperreflectivity on IR at the locations corresponding to IHRF on OCT, 301 (61.0%) of the IHRFs demonstrated evidence of hyperpigmentation on CFP, while only 115 (23.3%) showed evidence of hyperreflectivity on IR. The qualitative determination of the presence or absence of an abnormality on CFP or IR were significantly different (p < 0.0001). 327 (66.2%) of the IHRF showed hypotransmission, and 80.4% of these IHRF showed hyperpigmentation on CFP, though only 23.9% (p < 0.0001) demonstrated hyperreflectivity on IR. Conclusions Less than two‐thirds of IHRF evident on OCT manifest as hyperpigmentation on colour photos, though IHRF with posterior shadowing are more likely to be evident as pigment. IR imaging appears to be even more poorly sensitive for visualizing IHRF.